2011
DOI: 10.1111/j.1399-0004.2010.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

19p13.2 microduplication causes a Sotos syndrome‐like phenotype and alters gene expression

Abstract: Up to 90% of individuals affected by Sotos syndrome have a pathogenic alteration of NSD1 (encodes nuclear receptor-binding Su-var, enhancer of zeste, and trithorax domain protein 1), a histone methyltransferase that functions as both a transcriptional activator and a repressor. Genomic copy number variations may also cause a Sotos-like phenotype. We evaluated a three-generation family segregating a Sotos-like disorder characterized by typical facial features, overgrowth, learning disabilities, and advanced bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Moreover, several studies have demonstrated various genetic abnormalities including epigenetic alteration of KCNQ1T1, microduplication of 19p13.2, and a STK11 mutation in patients with Sotos-like features. [25][26][27] Therefore, further genetic investigation is needed for the patients without NSD1 mutation, while epigenetic alteration of KCNQ1T1, which is known to be the cause of BeckwithWiedemann syndrome, did not be found in our three patients.…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, several studies have demonstrated various genetic abnormalities including epigenetic alteration of KCNQ1T1, microduplication of 19p13.2, and a STK11 mutation in patients with Sotos-like features. [25][26][27] Therefore, further genetic investigation is needed for the patients without NSD1 mutation, while epigenetic alteration of KCNQ1T1, which is known to be the cause of BeckwithWiedemann syndrome, did not be found in our three patients.…”
Section: Discussioncontrasting
confidence: 62%
“…Lehman et al [] describe a familial 1.9 Mb duplication on chromosome 19p13.2 which causes features similar to Sotos syndrome. In a report describing a patient of Gomez–Lopez–Hernandez syndrome, a partial duplication of 19p13.2 is described, but its size is not reported and it is discarded as a polymorphism [Schell‐Apacik et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal radiographs are required to make the diagnosis. The differential diagnosis mainly includes Sotos syndrome, Weaver syndrome, and 19p13.2 microduplications (Lehman et al, 2012). Airway support is required in the majority of cases either by tracheostomy or by a tube that keeps the nasopharyngeal airway open.…”
Section: Discussionmentioning
confidence: 99%